(untitled) (Eurasian Medical Research Periodical, 2022)
The spleen is one of the most complex peripheral organs of the immune system. The paucity and inconsistency of information regarding the structure of the spleen is due to the fact that the study of its structure is mainly carried out in various types of laboratory animals, followed by extrapolation of the data obtained to humans. Single studies performed using histological material of the human spleen do not fully reflect all aspects of the morphometric study of the size of the organ pulp compartments and the state of its cellular composition [Silva J.S., Andrade A.C., Santana C.C., 2012]. The article presents a review of the literature on the morphometric state of the lymphoid tissue of the spleen in the condition of polypharmacy